Derecho privado y modernización : América Latina y Europa en la primera mitad del siglo XX - Duve, Thomas, 1967-; Duve, Thomas, 1967-; Keiser, Thorsten, 1974-; Keiser, Thorsten, 1974-; Rosario Polotto, María (Book collections on Project MUSE., 2015)
The volume contains essays on the modernization of private law in Europe and Latin America from the viewpoint of legal history. Through a comparison between different forms of legal development in various normative und cultural contexts, the papers seek to open up new research perspectives on the concept of modernization in the ﬁeld of private law.